THE SOCIAL SIGNIFICANCE OF CLOTHING SYMBOLS IN KYRGYZ ETHNOETIQUETTE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article defines clothing as a part of culture and examines it as a form of decorative art that shapes personal beauty. The author also examines the origins of clothing and its place in history. The study conducted an in-depth analysis of the symbolic meaning and uniqueness of Kyrgyz clothing. It determined the meaning of each garment and its value in traditional Kyrgyz culture. The article emphasizes that the white kalpak, a men’s headdress, is more than just a headdress, but a part of our history, symbolizing the heights of the Kyrgyz mountains, white as mirrors, reflecting the loftiness of thought, the purity of the soul, and the unity of the people. The women’s headdress, the “ak elechek,” or married woman’s headdress (the national white turban), is considered a sacred symbol of motherhood.Furthermore, the national costumes of the Kyrgyz people are described in detail in the Epic of Manas. It describes the types of clothing suitable for the nomadic lifestyle of men and the names of military attire. At the same time, the epic also discusses the characteristics of women’s clothing
Keywords: ak kalpak, ak elechek, Shambhala, Umai Ene, Kydyr Ata, Manas, Kanykey